Electoral Rules and Corruption - Torsten Persson; Guido Tabellini; Francesco Trebbi (Center for Economic Studies and ifo Institute (CESifo), 2001)
Is corruption systematically related to electoral rules? A number of studies have tried to uncover economic and social determinants of corruption but, as far as we know, nobody has yet empirically investigated how electoral systems influence corruption. We try to address this lacuna in the literature, by relating corruption to different features of the electoral system in a sample from the late nineties encompassing more than 80 (developed and developing) democracies. Our empirical results are based on traditional regression methods, as well as non-parametric estimators. The evidence is consistent with the theoretical models reviewed in the paper. Holding constant a variety of economic and social variables, we find that larger voting districts - and thus lower barriers to entry - are associated with less corruption, whereas larger shares of candidates elected from party lists - and thus less individual accountability - are associated with more corruption. Altogether, proportional elections are associated with more corruption, since voting over party lists is the dominant effect, while the district magnitude effect is less robust.
Keywords: 330